2015
DOI: 10.1371/journal.pone.0128244
|View full text |Cite
|
Sign up to set email alerts
|

Swertisin an Anti-Diabetic Compound Facilitate Islet Neogenesis from Pancreatic Stem/Progenitor Cells via p-38 MAP Kinase-SMAD Pathway: An In-Vitro and In-Vivo Study

Abstract: Transplanting islets serves best option for restoring lost beta cell mass and function. Small bio-chemical agents do have the potential to generate new islets mass, however lack of understanding about mechanistic action of these small molecules eventually restricts their use in cell-based therapies for diabetes. We recently reported “Swertisin” as a novel islet differentiation inducer, generating new beta cells mass more effectively. Henceforth, in the present study we attempted to investigate the molecular si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Furthermore, this rapid differentiation was observed in both Activin-A and Swertisin that follow the AKT-MEPK-TKK pathway, elucidated in our previous report (Dadheech et al, 2015). Analysing the temporal protein expression from undifferentiated PREPs at day zero to completely mature islet clusters at day four confirmed high islet cluster forming fidelity.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Furthermore, this rapid differentiation was observed in both Activin-A and Swertisin that follow the AKT-MEPK-TKK pathway, elucidated in our previous report (Dadheech et al, 2015). Analysing the temporal protein expression from undifferentiated PREPs at day zero to completely mature islet clusters at day four confirmed high islet cluster forming fidelity.…”
Section: Discussionsupporting
confidence: 72%
“…The islets generated from Activin-A and Swertisin groups were functional that is expressed Insulin transcript and positive for hormones including INSULIN and GLUCAGON, expressed GLUT2 and NKX6.1 (β-cell marker) and demonstrated glucose-stimulated c-peptide secretion. We observed that Swertisin-induced islets were significantly superior across all the functional parameters, thus generating a better quality of islet clusters, which could effectively maintain glucose homeostasis (Dadheech et al, 2013(Dadheech et al, , 2015Lumelsky et al, 2001). We further, wanted to evaluate the efficacy of both PREPs homing toward the damaged pancreas and their islet neogenic potential in the in vivo diabetic mice model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to lineage tracing experiments, we examined the ß-cell differentiation potential of genetically labeled BMSCs using Activin-a growth factor, ex vivo, as previously reported [ 26 , 31 ]. Genome integrated GFP + BMSC showed effective cell clustering at day 2 deciphered into islet-like aggregates by day 4 till day 7, similar to the non-transfected control BMSC (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…GFP + BMSCs were assessed for in vitro islet differentiation and formation of ILCC using Activin-a (20 ng/ml) as described previously [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%